Comparison of Regulations and Implications of Polygamy in the Islamic Legal System, Continental European Law, and Anglo-Saxon Law - Sofia Gussevi; Dianra Dzulhijah; Firman Hidayatullah; Ujang Abidin (International Journal of Nusantara Islam, 2026)
This study analyzes the regulation of polygamy from the perspectives of Islamic law, Continental European (civil law), and Anglo-Saxon (common law) legal systems, while examining the social and legal implications arising from their different approaches. Using a normative legal method with a comparative juridical approach, the research analyzes primary and secondary legal sources, including the Qur’an, statutory regulations, court decisions, scholarly journals, and comparative family law literature. The study covers Muslim-majority countries (Indonesia, Malaysia, Tunisia, and Pakistan) and Western jurisdictions (France, Germany, the United Kingdom, and the United States). The findings show that polygamy regulations are shaped by each country’s legal culture, ideological orientation, and social values. Islamic legal systems generally permit polygamy under strict conditions through judicial supervision and administrative controls, whereas civil law and common law systems uphold monogamy as the fundamental principle of family law. These contrasting legal frameworks generate significant social and legal challenges, particularly for minority and immigrant communities practicing polygamy in Western countries, highlighting tensions between religious norms, state law, and human rights in the context of globalization and transnational mobility. The study recommends more adaptive and inclusive legal approaches that strengthen legal protection for women and children while accommodating diverse socio-religious contexts. It contributes to comparative family law by demonstrating that polygamy regulation extends beyond legal doctrine and reflects the dynamic interaction of religion, culture, the state, and human rights in contemporary global society.